Loss of Acta2 in cardiac fibroblasts does not prevent the myofibroblast differentiation or affect the cardiac repair after myocardial infarction. (October 2022) - Li, Yuxia; Li, Chaoyang; Liu, Qianglin; Wang, Leshan; Bao, Adam X.; Jung, Jangwook P.; Dodlapati, Sanjeev; Sun, Jiangwen; Gao, Peidong; Zhang, Xujia; Francis, Joseph; Molkentin, Jeffery D.; et al.
Abstract: In response to myocardial infarction (MI), quiescent cardiac fibroblasts differentiate into myofibroblasts mediating tissue repair. One of the most widely accepted markers of myofibroblast differentiation is the expression of Acta2 which encodes smooth muscle alpha-actin (SMαA) that is assembled into stress fibers. However, the requirement of Acta2 /SMαA in the myofibroblast differentiation of cardiac fibroblasts and its role in post-MI cardiac repair remained unknown. To answer these questions, we generated a tamoxifen-inducible cardiac fibroblast-specific Acta2 knockout mouse line. Surprisingly, mice that lacked Acta2 in cardiac fibroblasts had a normal post-MI survival rate. Moreover, Acta2 deletion did not affect the function or histology of infarcted hearts. No difference was detected in the proliferation, migration, or contractility between WT and Acta2 -null cardiac myofibroblasts. Acta2 -null cardiac myofibroblasts had a normal total filamentous actin level and total actin level. Acta2 deletion caused a significant compensatory increase in the transcription level of non- Acta2 actin isoforms, especially Actg2 and Acta1 . Moreover, in myofibroblasts, the transcription levels of cytoplasmic actin isoforms were significantly higher than those of muscle actin isoforms. In addition, we found that myocardin-related transcription factor-A is critical for myofibroblast differentiation but is not required for the compensatory effects of non- Acta2 isoforms. In conclusion, the Acta2 deletion does not prevent the myofibroblast differentiation of cardiac fibroblasts or affect the post-MI cardiac repair, and the increased expression and stress fiber formation of non-SMαA actin isoforms and the functional redundancy between actin isoforms are able to compensate for the loss of Acta2 in cardiac myofibroblasts. Graphical abstract: Unlabelled Image Highlights: Acta2 deletion in cardiac fibroblasts does not affect the post-MI cardiac function. Acta2 -null cardiac fibroblasts can undergo normal myofibroblast differentiation. Non- Acta2 actin isoforms compensate for the loss of Acta2 deletion.